Mass Spectrometry Metabolomics and Feature-Based Molecular Networking Reveals Population-Specific Chemistry in Some Species of the Sceletium Genus - Reddy, Kaylan; Stander, Marietjie A.; Stafford, Gary I.; Makunga, Nokwanda P. (Frontiers in Nutrition, 2022)
The Sceletium genus has been of medicinal importance in southern Africa for millennia as used by the indigenous Khoekhoen (formerly "Khoikhoi") and the Sān or Sākhoen people. Sceletium tortuosum (Aizoaceae), one of eight species in the genus has gained pharmaceutical importance as an anxiolytic and anti-depressant, and several isolated and identified compounds, predominantly the mesembrine alkaloids have been studied. S. tortuosum is used for the manufacture of herbal teas and dietary supplements and other phytopharmaceutical products. The occurrence, in wild and cultivated plants and contribution of the various mesembrine alkaloids to the various observed pharmacological activities is still largely understudied, this study thus aimed to provide a metabolomic characterisation of S. tortuosum and its sister species as these are not easy to distinguish using morphology alone. Plant samples of the genus Sceletium were collected from their natural habitat (succulent Karoo, South Africa) and analysed through liquid chromatography-mass spectrometry (LC-MS), using MSE fragmentation as a putative tool for chemical identities. Metabolomics-based analyses were able to distinguish collections of S. tortuosum and other species of the genus based on the collection site. The main distinguishing features were the presence of biomarkers such as mesembrine (m/z 290.1757; RT 5.10 min), mesembrenol (m/z 290.1763; RT 4.54 min) and mesembrenone (m/z 288.1596; RT 4.82 min). Although the metabolomic profiles varied according to the different localities, these metabolites occurred at variable quantitative levels in Sceletium ecotypes. Molecular networking, as a dereplication tool to annotate and visualize the chemical space across samples tested, provided the added advantage of being able to observe mesembrine alkaloid isomers and coeluting metabolites (from the joubertiamine group) that were difficult to discern without this application. By combining high-throughput metabolomics together with global and feature based-molecular networking, a powerful platform that is able to discern chemical patterns within and between populations, that may reveal chemotaxonomic relationships and allow for the discovery of new biomarkers that may be used for quality-assurance purposes in industries that employ S. tortuosum, specifically, for the manufacture of phytopharmaceutical and dietary products.